Business finance - Cayanan, Arthur S.; Borja, Daniel Vincent H. (Sampaloc, Manila : Rex Bookstore, Inc., 2017)
"Business Finance provides senior high school students with basic concepts on corporate finance, investment management, and personal finance. It also provides an extensive discussion on financial statement analysis and how to evaluate the company's quality of earnings. This worktext includes exercises and cases that depict the Philippine setting. Based on publicly available information, listed Philippine companies were used for some exercises and illustrations".
Includes bibliographical references.
English text.
Keywords: Business finance